A novel red emission fluorescent probe for monitoring carbon monoxide in living cells and zebrafish. Issue 25 (7th June 2021) - Chen, Jie; Gan, Yabing; Hong, Sai; Yin, Guoxing; Zhou, Li; Wang, Changze; Fu, Yuchuan; Li, Haitao; Yin, Peng
Abstract : Carbon monoxide (CO), a gaseous signal molecule, plays a crucial role in biological systems. Abstract : Carbon monoxide (CO), a gaseous signal molecule, plays a crucial role in biological systems. With the aim of unraveling its biological functions, a novel fluorescent probe for sensing CO was rationally designed and synthesized based on a coumarin derivative fluorophore merging tetrahydroquinoxaline unit and five-membered pyrrolidine. This fluorescent probe demonstrated a large Stokes shift (Δ λ = 132 nm), high quantum yield, red emission, high sensitivity and selectivity for CO with remarkable fluorescence turn-on. And the detection limit for CORM-3 is as low as 31.2 nM with the linear range of 0–30 μM. More importantly, this novel probe has been successfully applied to the fluorescence imaging of CO in HepG2 cells and zebrafish, providing a useful approach for the further understanding of the physiological and pathological roles of CO in living systems.